ANALISIS PENYEBAB HEPATITIS B IBU HAMIL (STUDY PHENOMENOLOGY) DI WILAYAH PUSKESMAS PERHENTIAN RAJA KABUPATEN KAMPAR - Fatma Nadia; Dina Anggina (Institut Kesehatan dan Teknologi Al Insyirah, 2021)
Hepatitis B is an infectious disease that attacks the liver can be acute and chronic and can cause cirrhosis (hardening of the liver) and liver cancer. Hepatitis B is quietly one of the leading causes of death, causing liver damage that occurs gradually over the past 20 years. Hepatitis B is transmitted directly from infected pregnant women as much as 90-95% has the potential to become chronic with the risk of various complications as well as a source of transmission of Hepatitis B during his life and even death in young adulthood. This study aims to obtain in-depth information and analyze the causes of hepatitis B in pregnant women (Phenomenology Study) at the Perhentian Raja District Health Center. Kampar was conducted from December 2019 until June 2020. This type of research is a qualitative study with a Phenomenology research design. The number of informants is 19 people determined by purposive sampling. Informant's knowledge, family history of Hepatitis B, and history of immunization are factors that cause hepatitis B in pregnant women. It is expected that Health Officers can increase socialization and counseling about infectious diseases of Hepatitis B in the community, so as to increase public knowledge in order to reduce the number of Hepatitis B among pregnant women.